PENGARUH PACKAGING, SOSIAL MEDIA FACEBOOK, BRAND IMAGE, KUALITAS PELAYANAN, WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN. - Abdul Wakilul Akbar; Muhajirin; I Dewa Nyoman Usadha (Universitas Mahendradatta, 2023)
The amount of company competition and the current pandemic situationforces every producer to be smart in choosing products to produce by carrying outvarious innovations and promotions, one of which is Ohadoku, which is food that carriesa retro style. This type of research uses associative research with a total of 110 samplesfrom all ohadoku consumers in Uma Ilopeta. The sampling technique used purposivesampling with the results of the t-test signifthat all independent variables have a significant effect on the dependent variable.